Caracterización morfológica e hidrológica de la cuenca del río pastaza loreto, Perú 2007-2008, para determinar alternativas ambientales de manejo - Soplin Ríos, José Antonio (2008)
Since hydrographical basins are open systems and basic units of the physical geography with morphological and hydrological characteristics as landscape elements where climate and rainfall acting against the physiography are influent, the evaluation of these basins is important in order to identify possible risks. Then, this research aims to set environment management alternatives; Morphological and hydrological characterization of the basin was carried out using the qualitative, quantitative, quasi experimental method. Data of surface water samples were gathered in two field trips carried out in March and November 2007, respectively. Stations and water bodies along the basin and the sub basins were georeferenced. The existence of 15 sub basins with a good hydro energetic potential were identified, with slopes in the river bed of 0,35% which can generate electric power up to 500W.Three types of water: white, black and mixed were also identified with physical and chemical characteristics within the maximum allowable limits, according to the water classification for Class VI. The Pastaza river is navigable for less than 4-feet-draft boats. An inappropriate water quality of the whole basin was identified in the bacteriological characterization. Erosion amount caused by rain is 1,8 x 10-3 t/year of erode matter. According to the Horton Law, rivers of the third, fourth and fifth orders were also identified. This characterization allowed pointing up the importance of the basin as an environmental alternative for a sustainable development.